Effect of selenium supplement on proteome of chicken liver - Gulyás, Gabriella; Czeglédi, Levente; Prokisch, József; Jávor, András (Acta Agraria Debreceniensis, 2012)
The aims of the present study were to optimize a two dimensional polyacrylamide gel electrophoresis method to chicken liver proteome and to determine the changes of protein expression caused by selenium. Twelve broiler chicken were used in this experiment. The selenium intake was 0,2 mg/kg in the control group (6 chicken) and 4,25 mg/kg in the experimental group (6 chicken). Using the optimized proteomic approach, we have succesfully separated 747 proteins in the experimental group and 741 proteins in the control group. We found six proteins, wich expressed only in the samples of experimental group. Further investigations need to determine these six proteins with mass spectrometry (MS) and look for the correlation between the physiological effects of selenium and the expression of these proteins.